Sustainable Quality of Work Life and Job Satisfaction [an Indian Case Study] - Sadri, Sorab; Goveas, Conrad (Journal of Economic Development, Environment and People, 2013)
As HR experts would propound, organizational success is highly dependent on attracting, recruiting, motivating, and retaining its workforce. The quality of work life (QWL) pertains to favourable or unfavourable work environment in keeping employees motivated so as to enable increase per capita productivity. It aims at achieving an effective work place environment that satisfies both the organizational and personal needs and values of employees , promoting well being by job security, job satisfaction, development and thereby helping to maintain a better balance between work and non-work life. The word sustainability is derived from the Latin sustinere (tenere, to hold; sus, meaning up. Dictionaries provide more than ten meanings for sustain, the main ones being to “maintain", "support", or "endure”. However, since the 1980s sustainability has been used more in the sense of human sustainability on planet Earth and this has resulted in the most widely quoted definition of sustainability as a part of the concept sustainable, that of the Brundtland Commission of the United Nations on March 20, 1987: “sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their needs.